ENGLISH PRE-SERVICE TEACHERS IDENTITY DURING TEACHING PRACTICE: NARRATIVE RESEARCH - Brigitta Shinta Hapsari; Ouda Teda Ena (IJIET (International Journal of Indonesian Education and Teaching), 2019)
This research attempts to discover the identities of pre-service teachers in a private university in Yogyakarta, in relation to their positioning of their students. In addition, this research also aims to study to what extent positioning can construct identities of the pre-service teachers. The participants of this research were two pre-service teachers of a private university in Yogyakarta. The data were obtained through interview. The findings of this research first showed that the pre-service teachers perceived various identities in relation to positioning of their students. However, it was found that there were different identities between the two participants even though they faced similar problems. Last, positioning might have a force for the pre-service teachers in constructing their identities.DOI: doi.org/10.24071/ijiet.2019.030102